The study of heat penetration in palm oil fruitlets by developing a new technique for measuring oil content in fruiltlets during sterilization process - Abd. Aziz, Mustafa Kamal; Morad, Noor Azian; Mohd. Yunus, Sabariah; Abd. Razak, Abdul Syukor (Universiti Teknologi Malaysia, 2003)
Sterilization in palm oil milling is the most important unit process because its initial and crucial influence on oil palm bunch fruitlets will determine the efficiency and effectiveness of the downstream milling process and even to the refining process in producing high grade palm oil. As an example, improper processing leading to high free fatty acids content will increase bleaching and deodorization cost in refining. As a consequence, a breakthrough in continuous sterilization will improve steam stability and efficiency of the mill and reduce labor in the sterilization operation among other process and cost benefits. In an on-going research contract with Kumpulan Guthrie Berhad (K.G.B.), a continuous sterilizer prototype fitted with a multiple fluids curtain attachment was built in the C.L.E.A.R laboratory. This is to study the viability of various gases and fluid injected in a jet curtain to retain sterilizing steam within the continuous sterilizer yet allow FFB to exit. Air, hot water and varying steam pressures were tested. The design is to exploit the thermodynamics of thermal and pressure equilibrium of the fluids to act as a counter-force to impede and retain the pressure and heat content of the escaping steam.The air curtain concept is extensively used in pollution and aeronautics to blend polluted emissions with clean air to lower black smoke and to reduce heat signature of aircraft exhaust. The prototype was rigged to an extensive temperature, pressure and flow rate measurement array to ascertain the velocity, temperature and pressure profiles of the steam and fluid. Hot water and compressed air were found to be the good insulators and retainers of the escaping steam based on the profiles obtained. Both limits the steam from escaping as well as delay premature steam condensation causing pressure reduction in the sterilizer. Apart from the temperature and pressure of the jet curtain, its efficiency also lies with the type of nozzles, arrangement of curtain jet and gap, all of which was investigated. This process is greatly enhanced when the FFB is crushed and pre-treated which has been the on-going K.G.B. project with C.L.E.A.R. since 1996.